Omental adipose tissue is a more suitable source of canine Mesenchymal stem cells - Bahamondes, Francisca (2017)
Background: Mesenchymal Stem Cells (MSCs) are a promising therapeutic tool in veterinary medicine. Currently the subcutaneous adipose tissue is the leading source of MSCs in dogs. MSCs derived from distinct fat depots have shown dissimilarities in their accessibility and therapeutic potential. The aims of our work were to determine the suitability of omental adipose tissue as a source of MSCs, according to sampling success, cell yield and paracrine properties of isolated cells, and compared to subcutaneous adipose tissue. Results: While sampling success of omental adipose tissue was 100% (14 collections from14 donors) for subcutaneous adipose tissue it was 71% (10 collections from 14 donors). MSCs could be isolated from both sources. Cell yield was significantly higher for omental than for subcutaneous adipose tissue (38 ± 1 vs. 30 ± 1 CFU-F/g tissue, p < 0.0001). No differences were observed between sources regarding cell proliferation potential (73 ± 1 vs. 74 ± 1 CDPL) and cell senescence (at passage 10, both cultures presented enlarged cells with cytoplasmic vacuoles and cellular debris). Omental- and subcutaneous-derived MSCs expressed at the same level bFGF, PDGF, HGF, VEGF, ANG1 and IL-10. Irrespective of the source, isolated MSCs induced proliferation, migration and vascularization of target cells, and inhibited the activation of T lymphocytes. Conclusion: Compared to subcutaneous adipose tissue, omental adipose tissue is a more suitable source of MSCs in dogs. Since it can be procured from donors with any body condition, its collection procedure is always feasible, its cell yield is high and the MSCs isolated from it have desirable differentiation and paracrine potentials.